Precise test of lepton flavour universality in W -boson decays into muons and electrons in pp collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Ackermann, Anke; Baltes, Lisa Marie; Bartels, Falk; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (The European physical journal. C, Particles and fields, 2024)
The ratio of branching ratios of the W boson to muons and electrons, R μ/e W = B(W → μν)/B(W → eν), has been measured using 140 fb−1 of pp collision data at √s = 13 TeV collected with the ATLAS detector at the LHC, probing the universality of lepton couplings. The ratio is obtained from measurements of the t ¯t production cross-section in the ee, eμ and μμ dilepton final states. To reduce systematic uncertainties, it is normalised by the square root of the corresponding ratio R μμ/ee Z for the Z boson measured in inclusive Z → ee and Z → μμ events. By using the precise value of R μμ/ee Z determined from e+e− colliders, the ratio R μ/e W is determined to be R μ/e W = 0.9995 ± 0.0022 (stat) ± 0.0036 (syst) ± 0.0014 (ext). The three uncertainties correspond to data statistics, experimental systematics and the external measurement of R μμ/ee Z , giving a total uncertainty of 0.0045, and confirming the Standard Model assumption of lepton flavour universality in W - boson decays at the 0.5% level.
ATLAS Collaboration: G. Aad, A. Ackermann, L.M. Baltes, F. Bartels, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, L. Sanfilippo, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser und weitere 2879
Gesehen am 14.10.2025